2004
DOI: 10.2473/shigentosozai.120.461
|View full text |Cite
|
Sign up to set email alerts
|

CO<sub>2</sub> Gas Permeability and Adsorption of Coal Samples in Consideration of CO<sub>2</sub> Sequestration into Coal Seams

Abstract: It has been clarified that coal seams have a significant ability of CO 2 adsorption more than CH 4 as approximately double based on some experiments reported. By utilizing this property, coal bed methane gas can be replaced with CO 2 injected and produced as a clean energy.The demonstration project has already has been proceeded in North America, Europe and Japan. In Japan, coal seams, where mining is difficult economically, reserves about 18 billion ton, and it has been estimated that CO 2 sequestration into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…15 with comparisons to previous measurements by Somerton et al (1975) and Sasaki et al (2004). It was shown clearly; especially for Vietnamese coal core samples, that the stress attenuation coefficient for low permeability cores has larger values than those of high permeability cores.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…15 with comparisons to previous measurements by Somerton et al (1975) and Sasaki et al (2004). It was shown clearly; especially for Vietnamese coal core samples, that the stress attenuation coefficient for low permeability cores has larger values than those of high permeability cores.…”
Section: Discussionmentioning
confidence: 67%
“…Gas permeability also is important for estimating of the gas drainage rate or gas recovery ratio from coal seams. However, gas permeability is related to many factors, such as the cleat and fracture systems (Harpalani and Chen, 1997;Olson et al, 2009); porosity, gas pressure and mechanical stress (Somerton et al, 1975;Palmer and Mansoori, 1998;Sasaki et al, 2004); fracture orientation (Laubach et al, 2004). Philip et al (2005) investigated the effect of diagenesis on the initial flow properties of the fracture system, especially with respect to diagenetic effects on the connectivity of the fracture network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the permeability of coal to gas species is dependent on several factors, including cleat and fracture systems (Harpalani and Chen, 1997;Olson et al, 2009), porosity, type of gas and pressure and mechanical stresses (Somerton et al, 1975;Palmer and Mansoori, 1998;Sasaki et al, 2004), fracture orientation (Laubach et al, 1998), and the effects of matrix swelling/shrinkage induced by gas sorption. The permeability of coal can decrease with an increase in the effective stress (e.g., McKee et al, 1988;Jasinge et al, 2011).…”
Section: Introductionmentioning
confidence: 99%